Self‐Doped Conducting Polymer as a Hole‐Extraction Layer in Organic–Inorganic Hybrid Perovskite Solar Cells. Issue 9 (10th February 2016) - Lim, Kyung‐Geun; Ahn, Soyeong; Kim, Hobeom; Choi, Mi‐Ri; Huh, Dal Ho; Lee, Tae‐Woo
Abstract : Organic–inorganic hybrid perovskite solar cells are fabricated using a water‐soluble, self‐doped conducting polyaniline graft copolymer based on poly(4‐styrenesulfonate)‐ g ‐polyaniline (PSS ‐g‐ PANI) as an efficient hole‐extraction layer (HEL) because of its advantages, including low‐temperature solution processability, high transmittance, and a low energy barrier with perovskite photoactive layers. Compared with conventional poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) dispersed in water solution, PSS ‐g‐ PANI molecules are dissolved in water because of the polymeric dopant covalently bonded with PANI, and can steadily remain as an initial solution during long‐term storage and over a wide pH range to fabricate a HEL with fewer surface defects. The built‐in potential and device characteristics are substantially improved because of the surface energy state of PSS ‐g‐ PANI below Fermi‐energy level. Moreover, the PSS ‐g‐ PANI mixed with electron‐withdrawing perfluorinated ionomer (PFI) exhibits a higher work function (5.49 eV) and deeper surface energy state below the Fermi level; thus, an ohmic contact at the HEL/methylammonium lead iodide perovskite interface is obtained. Finally, the power conversion efficiency was increased from 7.8% in the perovskite solar cells with PEDOT:PSS to 12.4% in those with the PSS ‐g‐ PANI:PFI. Abstract : A water‐soluble self‐doped poly(styrene sulfonate) grafted polyaniline copolymer (PSS‐ g ‐PANI) was used to achieve high power conversion efficiency (PCE) in solution‐processed planar heterojunction perovskite solar cells. The PCE was increased from 7.8% in the methylammonium lead iodide perovskite solar cell with poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) to 12.4% in that with PSS‐ g ‐PANI:perfluorinated ionomer due to good energy level alignment at the hole extraction interface and high transmittance.